A commentary on Plutarch's De latenter vivendo - Roskam, Geert (Plutarchea hypomnemata., 2007)
Plutarch''s De latenter vivendo is the only extant work from Antiquity in which Epicurus'' famous ideal of an ''unnoticed life'' (lathe biosas) is thematised as such. Moreover, the short rhetorical work provides a lot of interesting information about Plutarch''s polemical strategies and about his own philosophical convictions in the domains of ethics, politics, metaphysics, and eschatology. In this book, Plutarch''s anti-Epicurean polemic is understood against the background of the previous philosophical tradition. An examination of Epicurus'' own position is followed by a discussion of Plutarc.